PENGEMBANGAN INSTRUMEN TES UNTUK MENGUKUR KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Gadis Niyanti Pertiwi; Nuryani, Nuryani; Edi Rohyadi; Yuyu Yuhana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to produce a test instrument to measure students' higher order thinking skills in the field of mathematics to produce a test instrument to measure problem solving skills by looking at the development procedure and the quality of the developed mathematical problem solving test instrument. The type of research used is the development of test instruments to measure mathematical problem solving skills. The test subjects in this study were fifth grade students of Banjar Agung 2 State Elementary School, Serang City, totaling 30 students. Based on the results of the trials conducted, it was found that: (1) the math problem solving test instrument has been said to be